Comparing and framing best Corporate Social Responsibility practices from Third-Party Logistics Providers: A case study of Deutsche Post – DHL and Geodis - Latour, Vincent / VL (2012)
This paper focuses on CSR practices in the third-party logistics (3PL) industry. The purpose of the research is to apply a previously developed framework on Logistics Social Responsibility (LSR) to two companies: Deutsche Post-DHL and Geodis. The goal is to analyse their practices and identify similarities, as well as differences, that could be used to improve the current LSR framework for the 3PL industry. It aims at guiding other 3PL providers that would like to develop their CSR strategies and practices. The literature review provides arguments for the need of such an analysis. In fact, studies on 3PL providers and CSR practices are rather thematic-oriented and limited. The idea is to provide a practical overview of the best practices in the industry by benchmarking reports from two leading companies: DP-DHL and Geodis. The empirical data collected will be analysed and used to fill and improve the LSR framework. The main finding lead to the improvement of the LSR framework into a more detailed one that could be used to understand and apply more efficiently CSR strategies. This framework can be used by other 3PL providers to better understand their own CSR performance in comparison with leading competitors. The testing of the framework provided interesting examples of practices from both companies studied and allowed to gather their similar activities.